2021
DOI: 10.3389/fpsyg.2020.609715
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Mothers’ Parenting Stress: Differences Between One- and Two-Child Families in China

Abstract: This study aimed to investigate mothers’ parenting stress and explore its relationship with associated demographic variables in two-child families involving preschool children. A sample of 621 two-child families and a comparison group of 319 one-child families from China participated in the study; the children were aged between 3 and 7. The results showed that (1) mothers of two-child families had higher parenting stress than those of one-child families; (2) within the two-child families, demographic variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 29 publications
(14 reference statements)
2
29
0
3
Order By: Relevance
“…Better mental health was also significantly and positively associated with the ability to drive a car ( p 0.000, 95% CI 0.993, 1.315). As expected, the greater the number of dependents, the more likely older adults were to have lower levels of mental well-being ( p 0.003, 95% CI −0.060, −0.012); the literature suggests that the number of owned children in the family is frequently the source of anxiety and stress [ 75 ], which may affect mental health. Additionally, homeownership ( p 0.000, 95% CI −0.602, −0.271) was significantly related to older adults’ mental health status, but the relationship was negative.…”
Section: Resultsmentioning
confidence: 71%
“…Better mental health was also significantly and positively associated with the ability to drive a car ( p 0.000, 95% CI 0.993, 1.315). As expected, the greater the number of dependents, the more likely older adults were to have lower levels of mental well-being ( p 0.003, 95% CI −0.060, −0.012); the literature suggests that the number of owned children in the family is frequently the source of anxiety and stress [ 75 ], which may affect mental health. Additionally, homeownership ( p 0.000, 95% CI −0.602, −0.271) was significantly related to older adults’ mental health status, but the relationship was negative.…”
Section: Resultsmentioning
confidence: 71%
“…Hasil studi menunjukkan bahwa terdapat hubungan yang signifikan antara pendapatan keluarga dengan tingkat stres, keluarga dengan pendapatan lebih rendah cenderung memiliki stres yang tinggi (Silva, Cunha, Ramos, Pontes, & Silva, 2019). Studi lain menunjukkan bahwa ibu dengan pendapatan yang rendah cenderung memiliki tingkat stres pengasuhan yang lebih tinggi (Qian, Mei, Tian, & Dou, 2021). Li et al (2005dalam Qian, Mei, Tian, & Dou, 2021 menyatakan bahwa semakin tinggi tingkat pendidikan orang tua maka akan semakin rendah stres pengasuhan yang dialami.…”
Section: Pembahasanunclassified
“…Regarding family structure, parents with more than two kids undoubtedly have to pay more time and energy to meet the extra parenting demands. A recent study in China indicated that mothers from two-kids families had higher parenting stress than their one-child counterparts ( 23 ), while Krieg ( 24 ) found that mothers in both one-child and two-child families reported equivalent levels of stress. Besides, age interval between siblings also accounts.…”
Section: Introductionmentioning
confidence: 99%